Pengaruh Literasi Keuangan Dan Social Influence Terhadap Perilaku Menabung Mahasiswa Rantau (Survei pada Mahasiswa Universitas Siliwangi Asal Jabodetabek) - Handayani, Dea; Solihat, Ai Nur; Sartika, Sri Hardianti (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This research is motivated by the problems experienced by Siliwangi University students, especially overseas students from Jabodetabek, namely the low saving behavior of students. The purpose of this study was to determine the extent to which financial literacy and social influence affect the saving behavior of Siliwangi University students from Jabodetabek both partially and simultaneously. This study uses a survey type quantitative research method. The population in this study were Siliwangi University students from the Jabodetabek area. The sampling technique used is probability sampling using simple random sampling with a sample size of 182 students. The data collection technique used a questionnaire and the data analysis technique used was multiple linear regression analysis. The results showed that: 1) Financial literacy has a significant effect on saving behavior 2) Social influence has a significant effect on saving behavior 3) Financial literacy and social influence have a significant effect on saving behavior.